The most important purpose of family in educating children to consideration social and natural environment - Dziekoński, Stanisław; Napiórkowski, Ryszard (Studia Ecologiae et Bioethicae, 2004)
The article comprehends the analysis of such problems as bringing up to love, moral bringing up of man, the importance of spiritual progress of man, forming to considering the responsibility for nature. Those problems are considered in the context of the importance of the social and natural environment.